The Effect of Enoxaparin on Inflammatory Marker, Apoptosis in Sw480 Colon Cancer Cell Line (Journal of Pharmaceutical Negative Results, 2022)
Background and Objectives: The world's fourth-deadliest malignancy is colon cancer (CC). is becoming more prevalent. salt enoxaparinHeparin in its fractionated low molecular weight (LMWH) form prevents factor Xa from contributing to clotting. enoxaparin inhibit viability of sw480 colon cancer cell line. Additionally, enoxaparin improved apoptosis while having little effect on cell-cycle progression, which raised doxorubicin's effectiveness. pro-inflammatory cytokines secretion during inflammatory reactions, including TNF-, IL-1, IL-1, and IL- 6. The most popular LMWH, enoxaparin, is known to prevent the release of several cytokines from T cells that are involved in inflammatory diseases like asthma, for example IL-4, IL-5, IL-13, and TNF. Materials and Methods: SW480 colon cancer and VERO normal cell line used; these cells were treated with diverse concentrations of enoxaparin to assess the impact of enoxaparin on the viability. Cell viability determines by MTT assay. SW480 cells were treated with different concentrations of enoxaparin the to assess the impact of enoxaparin on inflammation and apoptosis. cell lines were taken for immunoassay by ELISA method using TNF-alpha and caspase3. Results:enoxaparin has no significant effect on the viability of vero normal cell while significantly (P<0.050) reduce in viability of sw480 colon cancer cell.enoxaparin significantly (P<0.050) reduce in TNF-α and significant (P<0.050) increase in caspase3.Conclusion: Enoxaparin decrease viability of SW480 colon cancer cell line and have anti-inflammatory and apoptotic effect.